Changes in Biomass, Mineral Composition, and Quality of Cardoon in Response to NO3-:Cl- Ratio and Nitrate Deprivation from the Nutrient Solution - Borgognone, Daniela; Rouphael, Youssef; Cardarelli, Mariateresa; Lucini, Luigi; Colla, Giuseppe (Frontiers in Plant Science, 2016)
Leaf extracts of cultivated cardoon (Cynara cardunculus L. var. altilis DC) is an important source of phenols. Soilless culture represents an important and alternative tool to traditional agriculture, since it allows a precise control of plant nutrition and the maximization of yield and quality of the products. Reducing N supply, while keeping quantity as high as possible is desirable for environmental and health-related reasons, especially that N deficiency can lead to improved concentrations of secondary plant metabolites. Two greenhouse experiments were carried out in order to determine the effect of a decreasing NO3- : Cl- ratio (80:20, 60:40, 40:60 or 20:80) and nitrate deprivation (0, 5, 10 or 15 days before harvest) on biomass production, leaf chlorophyll content and fluorescence, mineral composition, and phytochemicals in leaves of cardoon ‘Bianco Avorio’ grown in a floating system. Total phenols, flavonoids and antioxidant capacity increased linearly with Cl- availability, especially when nitrate was replaced by 80% of chloride (20:80 NO3- : Cl- ratio), without having a detrimental effect on yield. Total nitrogen and nitrate concentration in leaves decreased linearly with increasing Cl- in the nutrient solution. Total phenols and antioxidant capacity recorded after 15 days of nitrate deprivation were higher by 43.1%, 42.8% and 44.3% and by 70.5%, 40.9% and 62.2%, at 59, 97 and 124 DAS, respectively compared to the control treatment. The decrease in leaf nitrate content recorded under N-deprivation occurred more rapidly than the reduction in total nitrogen. Thus, up to 15 days of nitrate withdrawal could lower nitrates without sharply reduce total nitrogen or affecting growth and biomass of cultivated cardoon. The use of N-free nutrient solution prior to harvest or the replacement of nitrates with chlorides could be adopted among growers to improve the quality of the product and enhance sustainability of crop production system.